Investigating the english language learning styles and learning strategies among IIUM students - Ahamad Shah, Mohamed Ismail; Esa, Zaleha; Ismail, Yusof ([s.n], 2012)
This study investigated the learning strategies, and the relationship between learning strategies and learning styles of Malaysian students studying English through Content-based Instruction (i.e. English for Academic Purposes and English for Occupational Purposes) at the International Islamic University Malaysia (IIUM). Learning styles and learning strategies of language learners play important roles in second language acquisition. The learning styles were investigated through an analysis of their responses (n=312) to Learning Styles Indicator (LSI) (Wintergerst et.a., 2003) while learning strategies were investigated through Strategy Inventory for Language Learning (SILL) (Oxford, 1990). These instruments have been validated in a number of studies. The study was mainly motivated by concerns about the standards of English among graduates who have been observed to be passive and reticent in the language classrooms. Specifically, the study investigated frequency of strategy use according to type of courses (i.e. content-based versus non content-based), gender, and proficiency levels. The study found that the students from the different degree programmes differed in the use of the six different strategies. The study also did not find any significant relationship between language learning strategies and gender. The research used Pearson’s correlation and multiple regression analysis to process the survey data. Results show that learning strategies and styles are inter-related and language instructors need to take cognizance of this connection in facilitating the learning experience of students. Almost half of the sample (n=312) adopt project orientation as their learning style. Out of all learning strategies only compensation strategy contributes statistically significantly towards all the three learning styles. However, the regression model shows that none of the learning strategies contributes significantly towards group activity orientation learning style. Results of the study imply that English instructors in particular need to be aware of the basics of strategies and styles to enable them to reinforce student learning experience.